The COVID-19 Pandemic and the Study of Suicidal Behavior: Analysis of Scientific Publications (Revista de Psicología, 2022)
In addition to the health challenge generated by the presence of COVID-19, the precarious mental health of many people prior to the pandemic, plus the conditions of uncertainty, isolation and biopsychosocial complications increased the risk of presenting alterations in all spheres. Recognizing that mental health is especially sensitive to elevated levels of stress and social maladjustment. Consequently, it may increase the incidence of suicidal ideation and behavior. Being a leading cause of death with devastating emotional and social costs. The objective of this study was to conduct a systematic review of the literature on suicide during coronavirus disease 2019. Our results inform the need to orient public health policies towards evidence-based suicide prevention strategies available in people with suicidal tendencies.
Keywords: Suicide; risk factors; mental health; prevention; COVID-19